Aspects of anorexia nervosa - Magdalena Wójcik; Grzegorz Boreński; Julita Poleszak; Przemysław Szabat; Marta Szabat; Joanna Milanowska (Kazimierz Wielki University, 2019)
Introduction: Eating disorders are severe psychiatric disorders. nervosa (AN) has a mortality rate among the highest of any psychiatric illness. Its etiology is multifactorial and not fully understood yet. Patients with AN have an intense fear of gaining weight and they continuously seek to their "ideal" weigh. Many studies focus on changes at the endocrine an neuronal level which can be a result of the illness or occur premorbid. The aim of the study: The purpose of this systemic review was to collect and analyse available data about aspects of anorexia nervosa. Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed database was carried out using the following keywords: anorexia nervosa, neuroimaging, endocrinology. Description of the state of knowledge: Emotional and psychological aspects of anorexia nervosa are very important in understanding this condition. Food restrictions may have a compulsive quality which were compared to those of obsessive-compulsive disorder (OCD), but with the focus on eating, weight and shape. Another aspects concerns neuronal alterations. Many studies with the use of neuroimaging showed changes in the right inferior prefrontal lobe, the right superior prefrontal lobe and the right parietal region, insula and orbitofrontal cortex in patients with anorexia nervosa. Also there is a variety of changes in endocrine system such as disturbances on the axis of Hypothalamic-pituitary-gonadal or growth hormone axis. Summary: The perception of anorexia nervosa has changed over year. It is known now that its etiology is complex. There are changes on many levels and it is still not known which one of them were premorbid. More studies are needed to have a better understanding of this condition and to be able to treat it better.